Immunomodulatory Effects of Dietary Phosphorus and Calcium in Two Strains of Laying Hens - Tanja Hofmann; Sonja Schmucker; Vera Sommerfeld; Korinna Huber; Markus Rodehutscord; Volker Stefanski (Animals, 2021)
Insufficient nutrient supply can impair the immune system, which is important for animal health and welfare. Since chicken can partly hydrolyze phytate, which is the primary phosphorus storage in plant seeds, a reduction of mineral phosphorus in the diets could be an option for more sustainable egg production. Laying hens require high concentrations of calcium that might inhibit the function of endogenous enzymes for phytate hydrolyzation. The objective of this study was to characterize the impact of standard and reduced dietary phosphorus and calcium concentrations on the number and functionality of immune cells in the peripheral and gut-associated immune system in a white and brown laying hen strain. Reduced mineral phosphorus enhanced several immune parameters such as B cells in blood and IgA concentrations in bile in both strains, and peripheral monocytes and T cells in cecal tonsils in brown hens. Reduced calcium levels resulted in lower numbers of T cells in blood and cecal tonsils in both strains, suggesting negative effects on adaptive immunity. Differences between the two strains were found in almost all immune parameters. Results suggest a potentially beneficial effect of reduced dietary mineral phosphorus on the immune system that is dependent on the genetic background.